Le risque d’attaques de requins à La Réunion - François Taglioni; Sébastien Guiltat (EchoGéo)
Reunion island is particularly exposed to shark attacks which have been more frequent than in any other area in the world. This article objectives are twofold. On the one hand it offers an analysis of the statistics of the 46 shark attacks between 1980 and 2014. Using the only interactive map created of these attacks to this day, several explicative variables that could condition the upsurge of attacks have been identified and analysed. On the other hand, this research analyses the institutional management of the shark crisis affecting Reunion Island since 2011. The creation of a natural marine reserve perceived as administrative and authoritarian crystallizes the shark attacks crises since 2011. A succession of on the spot reactions in the management of this crisis will illustrate that the government had an urgent management of the situation instead and in the place of a less passionate and more anticipated territorial governance which could doubtlessly have limited the magnitude and consequences of such a crisis.